INOVASI MANAJEMEN PENGAJARANDALAM PENINGKATAN PRESTASI SISWA KELAS 2 MADRASAH IBTIDAIYAH MUHAMMADIYAH (MIM) SABRANGLOR TRUCUK KABUPATEN KLATEN TAHUN 2016 - Suprianto, Suprianto (El-Hayah, 2018)
Abstract : Implementation of teaching management innovation in Madrasah Ibtidaiyah Muhammadiyah (MIM) Sabranglor Trucuk Klaten Regency 2016. This research formulate how and how far teaching management innovation in improving student achievement of second grade at Madrasah Ibtidaiyah Muhammadiyah (MIM)  Sabranglor Trucuk Klaten Regency 2016This research used qualitative method.  The research was conducted in Madrasah Ibtidaiyah Muhammadiyah (MIM) Sabranglor Trucuk Klaten Regency, from April to May 2017. Subject in principal research. As for informant in research student student, teacher, student. Data collecting technique by interview , Observation and documentation. Data validity techniques use Triangulation of data and Triangulation of sources. Data analysis techniques use interactive methods, data collection, data presentation, data reduction and conclusion.The results of the research are known (1) Innovation of teaching management in improving the achievement of second grade students in Madrasah Ibtidaiyah Muhammadiyah (MIM) Sabranglor Trucuk Klaten Regency in 2016 is done by Planning ie Innovation of teaching management not on physical form but also non-physical by teacher. In developing teacher potential to create innovation in learning. Organizing involves institutional arrangements in the organizational structure, management, development of teacher potential innovatively both from internal institutions and personnel. Implementation of activities before teacher learning is given many workshops, training, training on teacher innovation in teaching students, so that students can excel. Supervision is done by the principal to the teacher of the teaching teacher as well as from the supervisory department supervisor or supervision department which is scheduled every month by the supervisor of the education office.   Keywords: Innovation, teaching and achievement.